Rural Youth in Colombia: Inequalities and Challenges for Territorial Development - Salgado, Fredy Rafael Pacheco (Journal of Ecohumanism, 2024)
This article offers a comprehensive diagnosis of the socioeconomic conditions of rural youth in Colombia, with emphasis on their demographic distribution, access to basic services, education, employment, health, and their participation in the planning of public policies at the departmental level. Based on the review and analysis of secondary sources and official statistical data for the period 2020-2023, the main problems and inequalities that affect this population compared to their urban peers are identified. The results show significant gaps in multiple dimensions, which reaffirms the need to strengthen public policies with a differential and territorial approach, aimed at guaranteeing the effective inclusion and comprehensive development of rural youth as strategic actors in regional and national development processes.